European silent films on video : a critical guide - Parrill, William (McFarland & Co., 2006)
"This book is a critical encyclopedia of silent European films currently available on DVD, laser disc, and VHS. It provides summaries of the films, evaluates the quality of the prints, indicates the changing reputations of both films and filmmakers, evaluates individual films, and demonstrates how the techniques developed during the silent period continue to influence films today"--Provided by publisher